J. Moscheles - Sharp, William, 1749-1824 (artist):::Creator::::::::::::; Vigneron, Pierre Roch, 1789-1872 (artist):::Contributor:::::::::::: (Mori & Lavenu; London; United Kingdom)
Lithographed portrait of Ignaz Moscheles by W. (William?) Sharp based on the painting by Pierre Roch Vigneron.